The HLA‐A*26:132 allele identified in a volunteer donor for hematopoietic stem cell transplant. (21st June 2018) - Baek, I.‐C.; Choi, E.‐J.; Shin, D.‐H.; Kim, H.‐J.; Kim, T.‐G.
Abstract : HLA‐A*26:132 differs from HLA‐A*26:01:01:01 at nucleotides 269 and 346 in exons 2 and 3.